Strategies And Factors Of Explicatures In English-Arabic Subtitles Of The ‘Friends’ Sitcom On Netflix - Rahman, Ali Sukayna Abdel Kareem Abdel (2024)
Watching a subtitled work is often regarded as a form of communication between the target audience and the subtitles they read. To ensure this communication achieves its objective, subtitlers need to integrate context into subtitles, ensuring they are sufficiently explicit for viewers and minimizing reliance on literal translation whenever feasible. The present study aims to examine explicatures in the english- arabic subtitles of the sitcom friends on netflix, focusing on their areas, how they are prioritized by the subtitler, the strategies used for their presentation, and the factors behind their rendition. Explicatures can be broadly defined as the pragmatic developments of utterances. In the context of subtitling, they represent the subtitler's efforts to integrate actors' speech with contextual cues to elucidate meaning on the explicit side of utterances. To achieve its objectives, the study draws upon various theoretical frameworks, including relevance theory (rt), huang's typology of explicature areas (2007/2014), bogucki's model for decision-making in subtitling (2020), lomheim's model of subtitling strategies (1999), and klaudy's typology of explicitation categories (1998). These five frameworks interact and complement one another in that the first, rt, serves as the umbrella framework, having introduced the term 'explicature,' which is the central focus of the study. Huang's framework provides the classification of explicatures.